DISCOURSE MARKERS USED IN SHORT SERIES MOVIE ‘FRIENDS’ AND ITS RELATION WITH ENGLISH LANGUAGE TEACHING - Windy, .; ., Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: Language is primarily speech. This paper discusses discourse markers. They are used for various purposes like to create a smooth flow of thoughts and to make the interlocutors easily understand. This way is supposed to be handy in improving the speaking ability. The data were collected from a sitcom entitled ‘Friends’. They were analyzed in a descriptive and qualitative method. The data were classified and then described their function contextually. There are seventeen discourse markers encountered in sitcom. Yeah is the most discourse marker used and by the way is the least discourse marker used in the sitcom. Discourse markers are used to make the language of conversation to be natural. They are useful for the students to learn Thus, the use of discourse markers should be inserted and learned in the textbook for high schools. Keyword: Discourse markers, Communication, Short Series Movie, Sitcom, ‘Friends’, English Language Teaching Abstrak: Penelitian ini membahas tentang penggunaan ‘discourse markers’. ‘Discourse markers’ ini digunakan untuk berbagai keperluan diantaranya untuk menciptakan kelancaran dalam hal pikiran dan membuat lawan bicara agar lebih mudah memahami. Cara ini diharapkan dapat berguna dalam usaha meningkatkan kemampuan berbicara. Data yang dikumpulkan berasal dari film serial pendek berjudul ‘Friends’. Data tersebut dianalisa dengan menggunakan metode deskriptif dan kualitatif. Data tersebut kemudian diklasifikasi dan dipaparkan berdasarkan fungsinya. Ada tujuh belas ‘discourse markers’ yang ditemukan di dalam serial tersebut. ‘Yeah’ adalah ‘discourse marker’ yang paling banyak digunakan sedangkan ‘by the way’ adalah ‘discourse marker’ yang paling sedikit digunakan dalam serial tersebut. ‘Discourse markers’ digunakan dalam percakapan agar komunikasi dapat berlangsung lebih alami. Hal ini berguna bagi para siswa untuk dipelajari. Oleh karena itu, penggunaan ‘discourse markers’ seharusnya dimasukkan dan dipelajari di dalam buku pelajaran untuk tingkat atas (SMA). Kata Kunci : ‘Discourse Markers’, Komunikasi, Film Serial Pendek, Komedi Situasi, ‘Friends’, Pengajaran Bahasa Inggris.